POLA INTERNALISASI NILAI-NILAI AGAMA ISLAM PADA SUKU ANAK DALAM DI DESA TRANS SUBUR SP5 KECAMATAN KARANG DAPO KABUPATEN MUSI RAWAS UTARA - Yunen Pratama Sari (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2019)
The purpose of this study was to determine the role of community leaders in Islamic religious education in the Tribe of Anak Dalam. The respondents in this study were the village head, imam, chair of the study of mothers, community leaders. Data is taken, namely primary data and secondary data, data sources from respondents and informants, while the technique of managing data from interviews, observation, and documentation. Then the data analysis technique was used data reduction and data display or data presentation. And for the interpretation of data by interpreting it in the form of description. The results of this study are that religion in the Tribe of Anak Dalam at Trans Subur Sp5 Village Karang Dapo district has developed, because they have believed and believed in the existence of a God who governs the universe. From their enthusiasm in participating in religious activities, such as recitation for mothers and also learning the newspaper for children which fosters their curiosity about the teachings of Islam, and religious facilities such as mosques are still not used because they prefer the mosque Sp5 people, if they are good about morals, they are very concerned about their fellow Tribes and the surrounding community. But they will continue to be nurtured, by community leaders or for children at school.